2020
DOI: 10.1016/j.joen.2020.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Mature Permanent Teeth with Carious Pulp Exposure

Abstract: Vital pulp therapy (VPT) in mature permanent teeth with carious pulp exposure has been a matter of debate, with root canal therapy being the conventional standard of care. Previously reported negative outcomes for VPT in these teeth were based on data from studies that have used calcium hydroxide in direct pulp capping and partial and full pulpotomy. The introduction of hydraulic calcium silicate-based materials with sealing and bioactive potentials have opened a new era in VPT with more favorable results. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 66 publications
3
58
0
1
Order By: Relevance
“…Although the degree of bleeding has low specificity to predict the VPT outcome, excessive bleeding even after removal of superficial pulp tissue at the exposure site indicates that a more radical amputation is warranted in order to reach uniflamed pulp tissue (Taha et al . 2020). Control of haemorrhage for radicular pulps is paramount for the successful outcome of the pulpotomy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the degree of bleeding has low specificity to predict the VPT outcome, excessive bleeding even after removal of superficial pulp tissue at the exposure site indicates that a more radical amputation is warranted in order to reach uniflamed pulp tissue (Taha et al . 2020). Control of haemorrhage for radicular pulps is paramount for the successful outcome of the pulpotomy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, spontaneous pain is also subjective and difficult to evaluate quantitatively, highlighting the problem in selective caries removal for managing deep caries lesions. Taha et al (20) reported that "current pulp testing is not reliable to the extent that determining pulpal status has been described as 'at best an educated guess, ' and an urgent need exists for more definitive tests." A pulp examination method that includes an analysis of pulpal inflammatory biomarkers to assess the level of pulpitis intra-operatively is expected to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries shows high worldwide prevalence particularly in adults, according to epidemological studies. 1 Before exposure of pulp, carious process goes hand in hand with inflammation of the pulp. Inflammation severity escalates as the carious lesion advances towards the dental pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation severity escalates as the carious lesion advances towards the dental pulp. 1 If left untreated caries headway to extensive lesions, persuading inflammatory reactions in dental pulp. This leads to pulp necrosis, abscess formation and eventual loss of tooth 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation